Some Aspects Of The Breeding Biology Of Macrobrachium Rosenbergii (De Man) With Emphasis On Its Egg Incubation And Larval Rearing - Raffiq Ahmad, Kabir Ahmad (1985)
Ovarian maturation, artificial incubation of eggs and larval rearing of M. rosenbergii ( De Man ) were studied . Female prawns were categorised into seven arbitrary develop mental states based on the morphology of the gonads namely immatured females, matured females, pre-mating moult females , newly spawned females, females with orange colour eggs, females with grey colour eggs and post hatching females .The morphology and histology of the ovary for each developmental state was then studied . The mean oocyte size in the immature state was 47.0 + 1.3 urn and the oocyte size increased to a maximum o f 402.0 + 3.5 urn a t the pre-mating moult state . After oviposition , the oocyte size dimini shed to 49. 0+ 1.4 urn and then progressively increased Two series o f experiments were done to determine the optimum salinity and stocking density for artificial incubation of M. rosenbergii eggs . Newly laid eggs and 9 day old eggs were stocked at a density of 500/1 and incubated at 0 ppt , 6 ppt and 12 ppt salinity respectively .The mean percentage of hatching after 18 days of incubation for the newly fertilised eggs were 0% , 3% and 40% as compared to 2 % , 23% a n d 65% for 9 day old eggs .In the stocking density experiments , newly laid eggs were stocked at the rate of 1000/1 ,1 500/1 and 2000 / 1 at 1 2 ppt and their mean percentage of hatching were 37% , 33 % and 16% respectively. Comparative dietary studies of larval culture were done using the closed recirculating system and the modified green water system .The larval diets tested were Diet 1 : microcapsules , Diet 2 : egg custard and Artemia and Diet 3 : microcapsules and Artemia . Larvae fed exclusively microcapsules did not survive beyond six days of larval culture in both the systems .CONTOH There was no significant different ( P> 0 . 05 ) in t he production of juveniles between the two systems though higher production was obtained in the green water system . The mean number of juveniles obtained by Diet 2 using the green water system was 5 . 0/1 . When Diet 3 was used and larval culture was done using the green water system , the mean number of juveniles obtained was 2 . 5 /1 . The product ion of juveniles using Diet 2 was significantly higher ( P<0 . 05 ) than that o f Diet 3 .